Exploring Students' Perceptions Towards The Storytelling In English Language Learning - Setyani, Yeni; Kamil, Acep Bahrum (Peneliti.net, 2024)
One of the best methods for enhancing a student's language development while learning English is through storytelling. In order to find out how students felt about utilizing stories to learn English, the researchers in this study asked them. The study was based on the following research question: “What is the student’s perception towards storytelling in English Language Learning?” The method used in this research is qualitative. A semi-structured interview is used as a data collection tool. Twelve 8th-grade students from the SMP Negeri 1 Majalaya Karawang participated in this study. The two main findings suggest that the benefits of storytelling, and the effectiveness of storytelling. The study is designed to explore student academic performance.